2003
DOI: 10.1080/0959523031000154454
|View full text |Cite
|
Sign up to set email alerts
|

A prototype screening instrument for cannabis use disorder: the Cannabis Use Disorders Identification Test (CUDIT) in an alcohol‐dependent clinical sample

Abstract: The Cannabis Use Disorders Identification Test (CUDIT) was used for the first time as part of a randomized controlled trial for brief interventions in mild to moderate alcohol-dependent out-patients. This sample may be seen as a population at increased risk of cannabis use disorder. The CUDIT was developed by modifying the Alcohol Use Disorders Identification Test (AUDIT). The ability of the CUDIT to accurately screen for cannabis abuse or dependence was examined in the portion of the sample who reported some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
209
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(216 citation statements)
references
References 16 publications
1
209
2
4
Order By: Relevance
“…In a review of studies examining the fi ve-item Severity of Dependence Scale (Gossop et al, 1995) and the Problematic Use of Marijuana Scale (Okulicz-Kozaryn, 2007) for screening cannabis dependence in the general population, Piontek et al (2008) reported AUC values of .85 to .92, compared with .851 in the current study. However, screening for marijuana use using the 10-item Cannabis Use Disorders Identifi cation Test (Adamson and Sellman, 2003) in a clinical sample of alcoholics resulted in AUC values of .63 to .76 (Annaheim et al, 2008), lower than the AUC of .835 for use in the current study. At a cutpoint of 2 or more, a cocaine-specifi c version of the Severity of Dependence Scale resulted in a sensitivity and specifi city of 73% and 82%, respectively, in screening for cocaine dependence in a cross-sectional survey of past-6-month cocaine users (Kaye and Darke, 2002), compared with 76.0% and 86.0%, respectively, for drinking 5+/4+ drinks once or more a month.…”
Section: Discussioncontrasting
confidence: 61%
“…In a review of studies examining the fi ve-item Severity of Dependence Scale (Gossop et al, 1995) and the Problematic Use of Marijuana Scale (Okulicz-Kozaryn, 2007) for screening cannabis dependence in the general population, Piontek et al (2008) reported AUC values of .85 to .92, compared with .851 in the current study. However, screening for marijuana use using the 10-item Cannabis Use Disorders Identifi cation Test (Adamson and Sellman, 2003) in a clinical sample of alcoholics resulted in AUC values of .63 to .76 (Annaheim et al, 2008), lower than the AUC of .835 for use in the current study. At a cutpoint of 2 or more, a cocaine-specifi c version of the Severity of Dependence Scale resulted in a sensitivity and specifi city of 73% and 82%, respectively, in screening for cocaine dependence in a cross-sectional survey of past-6-month cocaine users (Kaye and Darke, 2002), compared with 76.0% and 86.0%, respectively, for drinking 5+/4+ drinks once or more a month.…”
Section: Discussioncontrasting
confidence: 61%
“…Inclusion criteria were ages 21-55 years; self-reported mean cannabis consumption Ն1 time/3 months but Յ3 days/week over the past 3 months (Cannabis Use Disorders Identification Test (18 )); selfreported "light" or "moderate" alcohol consumption according to a quantity-frequency-variability scale (19 ); or if "heavy," not more than 3-4 servings in a typical drinking occasion. Exclusion criteria included past or current clinically significant medical illness; history of clinically significant adverse event associated with cannabis/alcohol intoxication; Ն450 mL blood donation in the 2 weeks preceding drug administration; pregnant/nursing; interest in drug abuse treatment within the past 60 days; and currently taking drugs contraindicated with cannabis or alcohol (ethanol) or known to affect driving.…”
Section: Participantsmentioning
confidence: 99%
“…Inclusion criteria were ages 21-55 years; self-reported cannabis consumption Ն1 ϫ/3 months but Յ3 days/week over the past 3 months [Cannabis Use Disorders Identification Test (CUDIT) (21 )]; self-reported light or moderate alcohol consumption according to a quantity-frequency-variability scale (22 ), or if heavy consumption, a modal quantity not more than 3-4 servings in the majority of drinking occasions; licensed driver for Ն2 years with currently valid unrestricted license; and self-reported driving Ն1300 miles in the past year. Exclusion criteria included past or current clinically significant medical illness; history of clinically significant adverse event associated with cannabis/alcohol intoxication or motion sickness; Ն450 mL blood donation in 2 weeks preceding drug administration; pregnant/nursing; interest in drug abuse treatment within past 60 days; current cannabis or alcohol use disorder by CUDIT or Alcohol Use Disorders Identification Test (AUDIT) (CUDIT score Ͼ12; AUDIT score Ͼ12 for women/Ͼ14 for men); currently taking drugs contraindicated with cannabis or alcohol or known to impact driving; requirements for nonstandard driving equipment; and prior participation in a similar driving simulator study.…”
Section: Participantsmentioning
confidence: 99%